A Model for Developing Students Character in Vocational High Schools in Banten - Atep Iman; Iwan Ridwan; Kurniawan Putra Yudha; Ade Dwi Putra Janata (Journal of Innovative and Creativity, 2025)
This study aimed to develop and validate an integrated character development model for Vocational High School (SMK) students in Banten Province, Indonesia. A sequential exploratory mixed-methods design was employed, involving 4 teachers and 22 students from four purposively selected SMKs representing different regional and program characteristics. Qualitative data were collected through semi-structured interviews, focus group discussions, classroom observations, and document analysis. Quantitative data were collected using a validated 30-item Likert-scale questionnaire administered to 22 students. The qualitative findings identified five core character values prioritized by stakeholders: discipline, responsibility, honesty, cooperation, and hard work. However, systematic character education implementation remained limited, with only 35% of classes integrating character values explicitly. The study also identified challenges such as limited instructional time, inconsistent teacher modeling, and insufficient resources. Quantitatively, student perceptions indicated strong agreement (82.07%) toward existing character initiatives, although disparities appeared across dimensions such as personal experiences, teacher–student interactions, and developmental challenges.The resulting model consists of three components: (1) curriculum-integrated character instruction, (2) enhanced extracurricular activities with defined character outcomes, and (3) personalized student mentoring supported by family–school collaboration. Pilot implementation over four months demonstrated improvements in students’ character knowledge (23.4%), attitudes (18.7%), and behavioral indicators (15.3%). The findings suggest that character development in SMK settings requires intentional, structured, and contextually relevant strategies supported by teachers, administrators, families, and industry partners.